Remove common factors. The common factor is 3x. Then since you must keep the expression constant you put in parentheses what you must multiply 3x by to get each of the original parts of the expression.
So the answer must be 3x+3xy=3x(1+y).
The GCF is 3xy.
6y2+17y-14 = (2x+7)(3x-2) when factored
If that's -5, the answer is (x - 1)(3x + 5) If that's +5, it gets ugly in a hurry.
The GCF is 3x.
48x2+139+63 = (3x+7)(16x+9) when factored and worked out with the help of the quadratic equation formula
15x - 3xy = 3x(5 - y) 20 - 4y = 4(5 - y) 15x - 3xy + 20 - 4y = (3x + 4)(5 - y)
It is: 3x*(x+7)
The GCF is 3xy.
(3x - y+ 2)(3x + y + 2)
3(x2 + 3x + 1)
(3x + 1)(x + 5)
(x + 5)(3x + 1)
If that's -18y2, the answer is (3x - 2y)(x + 9y)
(3x + 3y)(x + y) = 3(x + y)2
(6x + t)(3x + t)
3x(2x + 1)
(3x - 2)(x + 8)